2016
DOI: 10.3389/fmicb.2016.01870
|View full text |Cite
|
Sign up to set email alerts
|

The Shifts of Diazotrophic Communities in Spring and Summer Associated with Coral Galaxea astreata, Pavona decussata, and Porites lutea

Abstract: The coral holobiont often resides in oligotrophic waters; both coral cells and their symbiotic dinoflagellates possess ammonium assimilation enzymes and potentially benefit from the nitrogen fixation of coral-associated diazotrophs. However, the seasonal dynamics of coral-associated diazotrophs are not well characterized. Here, the seasonal variations of diazotrophic communities associated with three corals, Galaxea astreata, Pavona decussata, and Porites lutea, were studied using nifH gene amplicon pyrosequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…An analysis of beta-dispersion [47] was used to quantify betweencommunity variations in the total and the active PADs communities, and a redundancy analysis (RDA) to explore the relationship between diazotrophic groups and environmental parameters. Statistical analyses in this study were performed using the R vegan package (v3.5.1) and an R-based pipeline, as previously described [46].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of beta-dispersion [47] was used to quantify betweencommunity variations in the total and the active PADs communities, and a redundancy analysis (RDA) to explore the relationship between diazotrophic groups and environmental parameters. Statistical analyses in this study were performed using the R vegan package (v3.5.1) and an R-based pipeline, as previously described [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some early studies demonstrated that biological N 2 fixation might play an important role in supplying bioavailable N within benthic reef habitats (Webb et al, 1975; Wiebe et al, 1975; Larkum et al, 1988), and more recently, diazotrophic bacteria have been shown to be an important constituent of the coral holobiont, supplying N requirements for symbiotic Symbiodinium (Lesser et al, 2004, 2007; Lema et al, 2012, 2014; Olson and Lesser, 2013; Zhang et al, 2016). However, within the pelagic environment of the GBR the role of biological N 2 fixation is less well-understood (Furnas et al, 2011), despite evidence to suggest that large discrepancies exist between nutrient availability and phytoplankton growth (Furnas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1:where R is the resulting ratio of nifH mRNA/ nifH DNA, E is the amplification efficiency, and ΔCt the cycle threshold difference between nifH mRNA and nifH DNA. The amplification efficiency was calculated using established standards, as described in [62]. The nifH RNA/DNA ratio of the main PADs groups was further calculated by multiplying the nifH RNA/DNA ratio obtained from the bulk community by the respective frequencies of the dominant groups (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of beta-dispersion [63] was used to quantify between-community variations in the total and the active PADs communities, and a redundancy analysis (RDA) to explore the relationship between diazotrophic groups and environmental parameters. Statistical analyses in this study were performed using the R vegan package (v3.5.1) and an R-based pipeline, as previously described [62].…”
Section: Methodsmentioning
confidence: 99%